Pathological survey on Temnodontosaurus from the Early Jurassic of southern Germany - Pardo Perez, Judith Mariana; Kear, Benjamin P.; Mallison, Heinrich; Gomez, Marcelo; Moroni, Manuel; Maxwell, Erin E. (My University, 2018)
Paleopathologies document skeletal damage in extinct organisms and can be used to infer the causes of injury, as well as aspects of related biology, ecology and behavior. To date, few studies have been undertaken on Jurassic marine reptiles, while ichthyosaur pathologies in particular have never been systematically evaluated. Here we survey 41 specimens of the apex predator ichthyosaur Temnodontosaurus from the Early Jurassic of southern Germany in order to document the range and absolute frequency of pathologies observed in this taxon as a function of the number of specimens examined. According to our analysis, most observed pathologies in Temnodontosaurus are force-induced traumas with signs of healing, possibly inflicted during aggressive interactions with conspecifics. When the material is preserved, broken ribs are correlated in most of the cases with traumas elsewhere in the skeleton such as cranial injuries. The range of cranial pathologies in Temnodontosaurus is similar to those reported for extinct cetaceans and mosasaurs, which were interpreted as traces of aggressive encounters. Nevertheless, Temnodontosaurus differs from these other marine amniotes in the absence of pathologies in the vertebral column, consistent with the pattern previously documented in ichthyosaurs. We did not detect any instances of avascular necrosis in Temnodontosaurus from southern Germany, which may reflect a shallow diving life style. This study is intended to provide baseline data for the various types of observed pathologies in large ichthyosaurs occupying the 'apex predator' niche, and potentially clarifies aspects of species-specific behavior relative to other ichthyosaurs and marine amniotes.
Keywords: None